2010
DOI: 10.1371/journal.pone.0013758
|View full text |Cite|
|
Sign up to set email alerts
|

Bringing the Hospital to the Patient: First Treatment of Stroke Patients at the Emergency Site

Abstract: BackgroundEarly treatment with rt-PA is critical for favorable outcome of acute stroke. However, only a very small proportion of stroke patients receive this treatment, as most arrive at hospital too late to be eligible for rt-PA therapy.Methods and FindingsWe developed a “Mobile Stroke Unit”, consisting of an ambulance equipped with computed tomography, a point-of-care laboratory system for complete stroke laboratory work-up, and telemedicine capabilities for contact with hospital experts, to achieve delivery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(112 citation statements)
references
References 20 publications
1
109
0
2
Order By: Relevance
“…Fassbender and coworkers developed a "mobile stroke unit" equipped with CT to perform prehospital thrombolytic therapies if indicated in a rural area. 20,21 Recently, the prehospital acute neurological therapy and optimization of medical care in stroke patients (PHANTOM-S) study introduced the stroke emergency mobile unit to apply prehospital thrombolysis in the Berlin inner-city catchment area. 22 The stroke emergency mobile unit is an advanced life support ambulance equipped with a CT scanner, point-of-care laboratory, and a mobile telecommunication support for teleradiology and teleconferencing.…”
Section: Discussionmentioning
confidence: 99%
“…Fassbender and coworkers developed a "mobile stroke unit" equipped with CT to perform prehospital thrombolytic therapies if indicated in a rural area. 20,21 Recently, the prehospital acute neurological therapy and optimization of medical care in stroke patients (PHANTOM-S) study introduced the stroke emergency mobile unit to apply prehospital thrombolysis in the Berlin inner-city catchment area. 22 The stroke emergency mobile unit is an advanced life support ambulance equipped with a CT scanner, point-of-care laboratory, and a mobile telecommunication support for teleradiology and teleconferencing.…”
Section: Discussionmentioning
confidence: 99%
“…11 Two studies have shown that prehospital CT scanning with an appropriately equipped ambulance is feasible and may allow for triage to an appropriate hospital and initiation of ICH-specific therapy. 12,13 …”
Section: Prehospital Managementmentioning
confidence: 99%
“…4 -7 These scores were tested with medical professionals in primary care, emergency medical services (EMS), and emergency department physicians. 7 Recent developments such as the installation of a CT scanner and point-of-care laboratory in EMS ambulances 8,9 promise a complete diagnostic stroke workup required for thrombolytic treatment before transport to the hospital. The possibility of sending such special ambulances to stroke emergencies might enable new prehospital stroke treatments to be evaluated, for example, ambulance-based neuroprotective trials.…”
mentioning
confidence: 99%